Exploring issues around Biblical, Western and African social values - Botha, J. Eugene (HTS teologiese studies, 2007)
This article explores the differences and similarities between the social value systems of the New Testament, the West and Africa. While it is acknowledged that the categories “The New Testament”, the “West” and “Africa”, are very broad general categories, it is possible to distinguish between them at a certain level of abstraction. It is shown that Biblical social values and traditional African social values are much closer to each other than they are to Western social values. This has enormous implications for the practising of theology and for the interpreting and use of Biblical texts.